A history of cant and slang dictionaries. Vol. III, 1859-1936 - Coleman, Julie (Oxford : Oxford University Press, 2008)
This third volume of this acclaimed history casts light on life across the globe, from Canadian and Australian settlers, London cockneys, & American schoolboys to New York ganglang, the narcotics trade, & the entertainment business.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English language -- Lexicography -- History; English language -- Early modern, 1500-1700 -- Lexicography; English language -- Slang -- History; Cant -- Great Britain -- History